STABILITY AND ADAPTABILITY ANALYSIS OF SOME QUANTITATIVE TRAITS IN UPLAND COTTON VARIETIES (Biological Sciences - PJSIR, 2001)
Five cotton varieties, all hirsutum types were compared for thei r adaptabi lity and stability parameters i n six environ ments over three year period for seed cotton yield, lint percentage and fibre length . The regression coefficient (b) was used as a factor for adaptability whereas the terms coefficient of determi nation (r2) and sum of squared deviations (S2d) from regression were used as a measure of stability parameters. Varieties, CRIS-121 and CRIS-SA were considered wel l adapted to all types of environments, Rehmani and NIAB-78, to less favourable environments and BH-89, to highly favourable environments. CRIS-121 and CRIS-SA were adaptable to highly favourable environments and other three varieties, to less favourable environments for l i nt . In respect of fibre length , CRIS-SA and Rehmani preferred high l y favourable environments and other varieties , to less favourable environment s. All the varieties had good stability in the test environments for yield and were more stable for lint percentage as compared to fibre length. CRIS-121 was generally more adaptable as well as stable for all the traits i n test environments.